Influence of dielectric constant of pore fluids on double-layer swelling: a validation study - Prakash, K.; Sridharan, A.; Philip, Jacob (Indian Geotechnical Journal, 2022)
The clay platelets are negatively charged, and hence, the behavior of clays is physicochemical in nature. The clay–pore liquid interaction depends upon pore medium chemistry, which is a function of many factors. Dielectric constant of the pore medium is one such important factor. The clay swelling is considered to be explained by the Gouy–Chapman theory of diffuse double layer. This paper intends to study the effect of dielectric constant of the pore fluid on the equilibrium sediment volume in light of diffuse double-layer equation of the Gouy–Chapman theory. It has been illustrated that the Gouy–Chapman theory cannot explain the equilibrium sediment volume behavior of montmorillonite and kaolinite clay minerals satisfactorily. It is also brought out that the equilibrium sediment volume behavior of these two clay minerals is quite opposite to each other.